A mulher nas comunidades primitivas: elementos para uma igualdade de gêneros - Silva, Yuri (2023)
Humankind emerged from primitive communities marked by primitive communism, characterized by the absence of social classes and private property. This equality extended to sociality, genders and education. With the advent of class society, the scarcity and non-existence of inequality in primitive communism were replaced by a new dynamic of exploitation. However, a return to these past forms is not feasible. The study of this previous social organization is valuable to guide the present, despite the contextual differences. The lesson of primitive communism lies in its ability to cultivate egalitarian relationships, signaling that, despite historical changes, humanity can achieve equality again. With the greater material wealth and technological development of our time, it is possible to build a more equitable future. By examining gender relations in primitive communities, a vital insight emerges for advancing contemporary gender equality, both in the educational sphere and beyond it. This historical knowledge provides a foundation for shaping emancipatory social practices. While not a matter of returning to the past, the past serves as a source of wisdom to nurture a fairer and more equitable future, where gender equality can be achieved in tandem with a more advanced material base.